2014
DOI: 10.1093/nar/gku1093
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical impact of C8-aryl-guanine adducts within the NarI recognition DNA sequence: influence of aryl ring size on targeted and semi-targeted mutagenicity

Abstract: Chemical mutagens with an aromatic ring system may be enzymatically transformed to afford aryl radical species that preferentially react at the C8-site of 2′-deoxyguanosine (dG). The resulting carbon-linked C8-aryl-dG adduct possesses altered biophysical and genetic coding properties compared to the precursor nucleoside. Described herein are structural and in vitro mutagenicity studies of a series of fluorescent C8-aryl-dG analogues that differ in aryl ring size and are representative of authentic DNA adducts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(218 citation statements)
references
References 72 publications
13
201
4
Order By: Relevance
“…This may have implications for the downstream cellular events similar to the recent studies that indicated the presence of bulky arylamine substitutions in the major groove prevent translesion synthesis [29,30]; (iii) Watson-Crick base-pair hydrogenbonds are more or less maintained in all three platinated-DNAs with the exception of the hydrogen-bond between the O2 atom of g6 and N2(H21) atom of C19 which was characterized by a drop in occupancy in all three platinated-DNAs. The hydrogen-bond between O4 atom of T8 and N6(H61) atom of A17 also showed a drop in occupancy with cisplatin-DNA and oxaliplatin-DNA adducts.…”
Section: Discussionmentioning
confidence: 71%
“…This may have implications for the downstream cellular events similar to the recent studies that indicated the presence of bulky arylamine substitutions in the major groove prevent translesion synthesis [29,30]; (iii) Watson-Crick base-pair hydrogenbonds are more or less maintained in all three platinated-DNAs with the exception of the hydrogen-bond between the O2 atom of g6 and N2(H21) atom of C19 which was characterized by a drop in occupancy in all three platinated-DNAs. The hydrogen-bond between O4 atom of T8 and N6(H61) atom of A17 also showed a drop in occupancy with cisplatin-DNA and oxaliplatin-DNA adducts.…”
Section: Discussionmentioning
confidence: 71%
“…26 In contrast, the chlorinated O-linked adducts strongly stalled insertion one base across from the lesion (at position 1; see numbering of template in Figure 4a, FLE by the polymerase adds 7 bases (up to position 7 on the gel)). Replication past [PCP]G was more strongly blocked than replication past [TCP]G, as some +6 and …”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
“…For example, approximately 12 and 16% of the extended primers were further extended to include four C bases opposite [TCP]G and [PCP]G, respectively, which is indicative of polymerase slippage. 26 In the presence of all four dNTPs (Figure 6c), [PhO]G was extended to create a full-length product. Extension past both chlorinated adducts increased, with faint bands detected corresponding to a full-length product.…”
Section: And a Benzo-[a]pyrene Diol Epoxide (Bpde) Adduct Of Da ([Bpdmentioning
confidence: 99%
See 2 more Smart Citations